Corporate Social Responsibility (CSR): A literature review - Halbusi, Hussam Al; Tehseen, Shehnaz * (Universiti Malaysia Sabah, 2017)
This paper aims to give an overview on the topic and impact of the corporate social responsibility on employee’s attitudes and behaviours (CSR), it can be noticed that different scholars still continue to look at the concept of CSR from different perspectives. In 1970, Milton Friedman was the first scholar who wrote an article regarding the responsibilities of corporations. After that academicians started to look at the concept of CSR in more details, and made a move from the general debates discussing about the legitimacy of CSR to other perspectives to get deeper understanding about the concept of CSR. But, most of the researches that have been conducted with regard to CSR were mainly focused on macro perspective with their great emphasis on the relationship between CSR initiatives and financial performance.